Perturbation effect of noise on overall feeling of discomfort from vertical whole-body vibration in vibro-acoustic environment - Aladdin, Mohd Farid; Abdul Jalil, Nawal Aswan; Guan, Ng Yee; Md Rezali, Khairil Anas (Elsevier, 2021)
The human discomfort from combined noise and vibration has been investigated with a new perspective. The concept in perturbation effect has been adopted to formulate a new novel predictive model of human discomfort from noise and vibration. A psycho-physics experiment has been designed to identify the perturbation effect which caused by noise stimulus. The subject was asked to be seated in a relaxed position, holding a handphone and used it to record all the response values after each stimulation. The finding suggested that the discomfort from vibration can be predicted with equation and the overall discomfort from noise and vibration is given by where the is the perturbation effect caused by noise stimulus.